2014
DOI: 10.1186/1745-6215-15-33
|View full text |Cite
|
Sign up to set email alerts
|

Methodological survey of designed uneven randomization trials (DU-RANDOM): a protocol

Abstract: BackgroundAlthough even randomization (that is, approximately 1:1 randomization ratio in study arms) provides the greatest statistical power, designed uneven randomization (DUR), (for example, 1:2 or 1:3) is used to increase participation rates. Until now, no convincing data exists addressing the impact of DUR on participation rates in trials. The objective of this study is to evaluate the epidemiology and to explore factors associated with DUR.MethodsWe will search for reports of RCTs published within two yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The results of the present study, because of the study design and larger sample size, confirmed the findings of Sultana study. In the before and after studies, considering the lack of parallel control group and random allocation process, the results are influenced by 2 main bias sources (regression to the mean and the effect of baseline values) (21,22). Therefore, such results are less reliable and valid.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study, because of the study design and larger sample size, confirmed the findings of Sultana study. In the before and after studies, considering the lack of parallel control group and random allocation process, the results are influenced by 2 main bias sources (regression to the mean and the effect of baseline values) (21,22). Therefore, such results are less reliable and valid.…”
Section: Discussionmentioning
confidence: 99%
“…However, as already stated, this latter justification is fundamentally unethical [2] because an honest null hypothesis does not exist at the start of the trial. Another reason to use unequal randomization is to increase patients' agreement to participate, but this argument is flawed, according to Hey and Kimmelman [18], in that to date, unbalanced randomization has not been found to increase patient recruitment, although this issue is presently under study [19]. Often, unbalanced randomization is justified because it allows for gathering more safety data on the new treatment.…”
Section: Discussionmentioning
confidence: 95%
“…They will also help in better defining how to assess risk of bias associated with MPD at the systematic review level and provide insight into the frequency with which MPD compromises trust in statistically significant meta-analytical results. Finally, the publication of this protocol will contribute to making the objectives and design of methodological surveys more transparent[ 2 , 8 , 21 24 ].…”
Section: Discussionmentioning
confidence: 99%